2015
DOI: 10.1016/j.jep.2015.07.032
|View full text |Cite
|
Sign up to set email alerts
|

Pereskia aculeata Miller leaves present in vivo topical anti-inflammatory activity in models of acute and chronic dermatitis

Abstract: This study showed that the acute and chronic anti-inflammatory activity of P. aculeata leaves is very promising, and corroborates to better understand their ethnopharmacological applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
45
0
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 49 publications
1
45
0
11
Order By: Relevance
“…Furthermore, there are reports of the utilization of some species of the genus Pereskia as a natural medicine against cancer (Pinto et al, 2012). In the past five years, several biological activities have been attributed to P. aculeata leaf extracts, including in vivo topical anti-inflammatory activity in models of acute and chronic dermatitis (Pinto, Machado, et al, 2015), wound healing activity (Pinto et al, 2016) and antinociceptive activity (Pinto, Duque, et al, 2015), in vitro T antioxidant (Pinto et al, 2012;Sousa et al, 2014), and antimicrobial potentials (Souza et al, 2016), added to the antiproliferative activity against leukemia, neuroblastoma, and breast cancer cell lines (Pinto et al, 2012;Souza et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, there are reports of the utilization of some species of the genus Pereskia as a natural medicine against cancer (Pinto et al, 2012). In the past five years, several biological activities have been attributed to P. aculeata leaf extracts, including in vivo topical anti-inflammatory activity in models of acute and chronic dermatitis (Pinto, Machado, et al, 2015), wound healing activity (Pinto et al, 2016) and antinociceptive activity (Pinto, Duque, et al, 2015), in vitro T antioxidant (Pinto et al, 2012;Sousa et al, 2014), and antimicrobial potentials (Souza et al, 2016), added to the antiproliferative activity against leukemia, neuroblastoma, and breast cancer cell lines (Pinto et al, 2012;Souza et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the aforementioned studies evidencing the nutritional and ethnopharmacological relevance of ora-pro-nobis leaves, information on their phytochemical constitution remains limited. The majority of the papers that performed chemical evaluation contemplated the amino acids and phytosterol profiles, also focusing on its essential oil (Pinto & Scio, 2014;Pinto, Machado, et al, 2015;Souza et al, 2016;Zem, Helm, Henriques, Cabrini, & Zuffellato-Ribas, 2017). A few works have indicated that phenolic compounds and carotenoids are the major antioxidant constituents of P. aculeata leaves (Agostini-Costa, Wondraceck, Rocha, & Silva, 2012;Pinto et al, 2012;Pinto, Duque, et al, 2015), however, to our best knowledge, an advanced characterization of its phenolic constitution is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Besides being used as food by poor people, it is also used in popular medicine as laxative, emollients, and to treat skin wounds and inflammation. 11,12 The use of plants for functional purposes in production of processed products can be a viable and easy option for prevention of diseases. The production of functional flours is useful since different products nutritionally enriched can be developed.…”
Section: Introductionmentioning
confidence: 99%
“…Ot is often referred to as "green meat" or "vegetable meat" due to its high protein content (Madeira et al, 2016). Research also indicates its leaves are an important source of fiber, calcium and iron Martin et al, 2017), bioactive compounds such as antioxidants and anti-inflammatory substances (Pinto et al, 2015). Encouragement of its use is seen as an important strategy to improve nutrition and income among poor people .…”
Section: Introductionmentioning
confidence: 99%